Sonographic abnormalities in augmented bladder using porcine intestinal submucosa (SIS) - Rossetto, V. J. V. [UNESP]; Souza, P. M. [UNESP]; Doiche, D. P. [UNESP]; Mamprim, M. J. [UNESP]; Padovani, C. R. [UNESP]; Brandao, C. V. S. [UNESP] (Arquivo Brasileiro Medicina Veterinaria Zootecnia, 2016)
Among the different materials for bladder augmentation, porcine intestinal submucosa (SIS) is the most widely investigated and stands out for its ability as a cell scaffold. In this context, the ultrasound examination allows the detection of changes from the surgical procedure, enabling the early verification of potential complications and evaluation of patient outcomes. The aim of this paper is to describe the main sonographic findings in dogs submitted to cystoplasty using acellular SIS and seeded with homologous smooth muscle cells at 30 (M30) and 60 (M60) days postoperatively. Sonographic changes included irregularities and thickening of bladder wall especially at M30. Additionally, were visualized urinary sediment and uroliths in animals submitted to acellular SIS cistoplasty. Abdominal ultrasonography was useful in the postoperative evaluation of animals undergoing cystoplasty with acellular or seeded SIS.
Keywords: dog; ultrasound; tissue repair; cell therapy; cystoplasty